2010
DOI: 10.1074/mcp.m900508-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Multiple, Non-conserved, Internal Viral Ligands Naturally Presented by HLA-B27 in Human Respiratory Syncytial Virus-infected Cells

Abstract: The recognition of short viral peptides associated with human histocompatibility complex (human leukocyte antigen (HLA) 1 ) class I molecules on the cell surface allows cytotoxic T lymphocytes (CTLs) to recognize and kill virus-infected cells (1). These peptides are generated by proteolytic processing of newly synthesized viral proteins in the cytosol by the combined action of proteasomes, ERAAP (endoplasmic reticulum aminopeptidase associated with antigen processing), and in some cases other peptidases (2). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 44 publications
0
60
0
Order By: Relevance
“…And lastly, the analysis of the immunoprevalence and immunodominance of the HLA class II response described in this report together with the HLA class I response from previous immunoproteomics studies (12,13,26) could have implications for vaccine development. The 3Ј core and intermediate genes translate 52% of the HRSV proteome; however, they include 94% and 100% of natural HLA class I and II , N (nucleoprotein), P (phosphoprotein), M (matrix protein), SH (small hydrophobic protein), G (glycoprotein), F (fusion protein), M2 (matrix protein 2), M2-2 (matrix protein 22k), and L (polymerase).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…And lastly, the analysis of the immunoprevalence and immunodominance of the HLA class II response described in this report together with the HLA class I response from previous immunoproteomics studies (12,13,26) could have implications for vaccine development. The 3Ј core and intermediate genes translate 52% of the HRSV proteome; however, they include 94% and 100% of natural HLA class I and II , N (nucleoprotein), P (phosphoprotein), M (matrix protein), SH (small hydrophobic protein), G (glycoprotein), F (fusion protein), M2 (matrix protein 2), M2-2 (matrix protein 22k), and L (polymerase).…”
Section: Discussionmentioning
confidence: 99%
“…5). In previous immunoproteomics studies (12,13,26), analyses of the HLA class I-restricted antiviral immune response against HRSV identified 16 natural viral ligands by mass spectrometry. This analysis showed that 12 of the HRSV ligands that were detected were included in proteins encoded by the 3Ј group, whereas only three and one of them were integrated into proteins that were encoded by the intermediate and 5Ј groups, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations